Increasing the Digital Capacity of the Pakem Happy Village Community Pacar Kembang Tambaksari Surabaya Through Website Production and Application Training: Peningkatan Kapasitas Digital Komunitas Pakem Happy Kelurahan Pacar Kembang Tambaksari Surabaya Melalui Pembuatan dan Pelatihan Penggunaan Website - Nasywa Salsabila; Aura Wahidah Nendrisyah; Salfiyatus Syarifah; Agnes Tresia Silalahi (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
The development of information technology has driven digital transformation in various sectors, including micro, small, and medium enterprises (MSMEs). However, many MSMEs still experience limited digital access and literacy. This community service activity aims to increase the digital capacity of MSMEs through the creation and training of the Pakem Happy Community in Pacar Kembang Village, Tambaksari District, Surabaya. The activity was carried out through stages of observation, design, development, training, and technical assistance. The result is the realization of the community website www.pakemhappy.com as a medium for information, promotion, and documentation of MSME activities. The interactive training successfully improved the digital literacy of participants and built a sense of ownership of the digital platform. This activity demonstrates the effectiveness of a community-based and participatory approach in encouraging inclusive and sustainable digital transformation among MSMEs.